2016
DOI: 10.1080/1060586x.2016.1195094
|View full text |Cite
|
Sign up to set email alerts
|

Perception of risks associated with economic sanctions: the case of Russian manufacturing

Abstract: This paper is focused on assessing the risk factors for Russian manufacturing firms posed by sanctions imposed on Russia by the EU, US, and other countries in 2014. While there is an extensive literature assessing the successes and failures of international sanctions on the economies of both those imposing and targeted by sanctions on a macroeconomic level, we are more interested in trying to understand the corporate response -i.e. which firms evaluate the introduction and increasing scale of economic sanction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…They showed that target companies reduced their revenues by one-third and asset values by half. Golikova and Kuznetsov (2017) confirmed that almost half of the companies investigated felt threatened by the risk of being negatively influenced by sanctions. They found that the size of the company and the geographical area of the business affect the firms' assessment, which especially concerns large companies with access to international markets, engaging in business with 5 The EU's sanctions are moderate because the member countries are afraid of its counter-effects although the impact varies among member countries (Hasselbach, 2014;Veebel and Markus, 2016).…”
Section: Literature Reviewsupporting
confidence: 55%
See 2 more Smart Citations
“…They showed that target companies reduced their revenues by one-third and asset values by half. Golikova and Kuznetsov (2017) confirmed that almost half of the companies investigated felt threatened by the risk of being negatively influenced by sanctions. They found that the size of the company and the geographical area of the business affect the firms' assessment, which especially concerns large companies with access to international markets, engaging in business with 5 The EU's sanctions are moderate because the member countries are afraid of its counter-effects although the impact varies among member countries (Hasselbach, 2014;Veebel and Markus, 2016).…”
Section: Literature Reviewsupporting
confidence: 55%
“…Ahn and Ludema (2017) and Golikova and Kuznetsov (2017) are among them. To tackle this research question, we gathered data by conducting an interview survey of Russian regional enterprises in late 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the influence of sanctions on companies in individual economy sectors, Golikova and Kuznetsov (2016) demonstrate that Russian companies most heavily involved in trade and technological chains with the European Union and the Ukraine will be hit the hardest by the sanctions. Sectoral sanctions may also cause economic disintegration with traditional trade partners, and sanctions against the defense industry may result in an increased brunt of defense spending for the country (Klinova and Sidorova, 2014).…”
Section: Sanctions and The Russian Economymentioning
confidence: 99%
“…The International Monetary Fund (IMF, 2015), Gurvich and Prilepskiy (2015), Mau and Ulyukaev (2015), and Mau (2017) examined how these various crisis-related events have affected Russia's overall economy, while Golikova and Kuznetsov (2017) investigated the impact specifically on manufacturing. Wegren, Nilssen, and Elvestad (2016) examined how Russian food security policy, which focuses on agricultural import substitution and self-sufficiency, has impacted the agricultural and food sector since Russia created its Doctrine on Food Security in 2010.…”
Section: Introductionmentioning
confidence: 99%